2020
DOI: 10.1111/appy.12411
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of modified electroconvulsive therapy for the refractory depression in older patients

Abstract: Background: To explore the clinical efficacy and safety of modified electroconvulsive therapy (MECT) in the treatment of elderly patients with refractory depression. Methods : A total of 43 older patients (18 male and 25 female) with refractory depression were enrolled in our study from March 2014 to February 2015, with the average age of 65±4.8 years old. Modified electroconvulsive therapy (MECT) was performed in these patients after physical examinations and anesthesia procedures. Hamilton Depression Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In line with this point, a recent meta‐analysis revealed that only 41% of depressed patients receiving psychotherapy experienced significant alleviation of depressive symptoms 14 . In terms of the physical therapy, the transcranial magnetic stimulation (TMS) and modified electroconvulsive therapy (MECT) had been confirmed to have significant effects on depression 15,16 . The side effects of these physical therapies included but not limited to cognitive impairment (especially in memory), discomfort of head and face, facial convulsions, and so on, 7 which would limit their application.…”
Section: Introductionmentioning
confidence: 95%
“…In line with this point, a recent meta‐analysis revealed that only 41% of depressed patients receiving psychotherapy experienced significant alleviation of depressive symptoms 14 . In terms of the physical therapy, the transcranial magnetic stimulation (TMS) and modified electroconvulsive therapy (MECT) had been confirmed to have significant effects on depression 15,16 . The side effects of these physical therapies included but not limited to cognitive impairment (especially in memory), discomfort of head and face, facial convulsions, and so on, 7 which would limit their application.…”
Section: Introductionmentioning
confidence: 95%
“…Finally, Chinese traditions in agricultural areas may have a protective effect on mental health of older adults (54,55). For instance, older adults usually live with family members in China; thus, they could have better social support than their counterparts in big cities, which could reduce the risk of poor mental health (56)(57)(58). Further, Chinese elderly are commonly well-respected and cared for by their families and children as traditional Chinese culture emphasizes filial piety and reverence for seniors (8).…”
Section: Discussionmentioning
confidence: 99%
“… 20–22 ECT is associated with a reduced risk of suicide in the year after discharge. 23 While there is strong evidence supporting the efficacy of ECT in middle-aged and older adults, 24 , 25 little is known about its efficacy and cognitive side-effects in younger adults (aged 18–30) with TRD. Previous studies have suggested that ECT in young adults improves clinical outcomes during the acute treatment phase.…”
Section: Introductionmentioning
confidence: 99%